1995
DOI: 10.1111/j.1439-0434.1995.tb00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Dependent Necrosis Formation by Magnaporthe grisea Toxin(s) in Rice cv. Sekiguchi‐asahi*

Abstract: The significance of light irradiation in neerosis formation by Magnaporthe grisea toxin(s) on rice cv. Sekiguchi‐asahi was investigated. The effective wave region for light‐dependent neerosis formation was 400 700 nm. An absorption band of the toxin(s) was restricted to the wave region shorter than 400 nm. Both of the phytosynthesis and necrosis formation were inhibited by photosynthetic inhibitors, and the inhibition of both activities was dependent on concentration of the inhibitors. The necrosis formation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 3 publications
1
13
1
1
Order By: Relevance
“…6b). Previously, the present authors have demonstrated that the spore germination¯uid of M. grisea induced Sekiguchi lesion-like necrosis in a light-dependent manner (Arase et al, 1990b;Iedome et al, 1995). Tryptamine also accumulated in leaf necrosis induced by the spore germination¯uid under light, whereas it did not accumulate in the leaves where leaf necrosis formation was suppressed by dark treatment (data not shown).…”
Section: Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…6b). Previously, the present authors have demonstrated that the spore germination¯uid of M. grisea induced Sekiguchi lesion-like necrosis in a light-dependent manner (Arase et al, 1990b;Iedome et al, 1995). Tryptamine also accumulated in leaf necrosis induced by the spore germination¯uid under light, whereas it did not accumulate in the leaves where leaf necrosis formation was suppressed by dark treatment (data not shown).…”
Section: Resultscontrasting
confidence: 46%
“…Tryptamine also accumulated in leaf necrosis induced by the spore germination¯uid under light, whereas it did not accumulate in the leaves where leaf necrosis formation was suppressed by dark treatment (data not shown). However, neither tryptamine accumulation nor leaf necrosis was induced in leaves that were pretreated with the protein-and photosynthetic inhibitors cycloheximide and 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) (Arase et al, 1993;Iedome et al, 1995), respectively, even under light (data not shown). Furthermore, tryptamine (600 lg/ml) induced Sekiguchi lesion-like necrosis in leaves of the rice sl-mutant under light.…”
Section: Resultsmentioning
confidence: 81%
“…Investigations using the M. grisea ‐cv. Sekiguchi‐asahi system demonstrated that toxins produced by germinating spores of the pathogen played an important role as the primary inducer of Sekiguchi lesion formation ( Arase et al, 1990a,b; Iedome et al, 1995). Vidhyasekaran et al (1986) reported that B. oryzae produced a host‐specific toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Light intensities were measured using a thermopile with a quartz window (MIR‐100Q, Mitsubishi Yuka Co., Ltd, Yokkaichi, Japan). Spectral energy distribution of the light sources and the filters' transmission ranges have been previously described ( Iedome et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Sekiguchi lesion‐like leaf necrosis has also been induced by treatment with various chemicals or with fungal toxins from germinating spores of M. grisea ( Kiyosawa, 1970; Arase et al, 1990a). Previous reports have demonstrated ( Arase et al, 1990b, 1997; Iedome et al, 1995) the significance of light irradiation in enhancing the formation of Sekiguchi lesion and necrosis in rice cv. Sekiguchi‐asahi.…”
Section: Introductionmentioning
confidence: 94%